The Effect of the Based Learning (RBL) Model to Improve Students' Critical Thinking Skills - Syamratulagi, Sofyan; Kamaluddin, Kamaluddin; komalasari , Lala intan; Swandi, Swandi; Rumakat, Maya (research, training and philanthropy institution Natural Aceh, 2025)
Critical thinking skills are needed to improve students' ability to face life's challenges in the 21st century. The RBL model offers another approach: students are placed as active subjects to improve critical thinking skills. This study aims to systemically design learning by integrating the principles and learning model of RBL to enhance critical thinking skills and investigate the effectiveness of the RBL learning model in improving students' critical thinking skills in various elementary schools. The research method used in this study is pre-experiment with a one-group pretest-posttest design. The sample of this research was conducted on about 20 fifth-grade students of SDN 03 Pekat. A critical thinking skills test and observation sheet were used to collect data to measure learning activities and analyze data using SPSS 25. The results showed that the difference in mean or average value from pretest (65.15) and posttest (82.7) showed that the RBL model affected students' critical thinking skills. Using RBL, students can be taught to analyze, evaluate, and solve problems. Thus, the RBL model can be used as an alternative learning model to improve critical thinking skills.